English majors [compact disc] - Keillor, Garrison (HighBridge, 2008)
Skits and bits from "A Prairie Home Companion" celebrate the secret society of men and women who possess excellent spelling and punctuation skills. With guest appearances by Allen Ginsberg, Billy Collins, Roy Blount Jr., Robert Bly, Donald Hall, and Calvin Trillin.